Dosa Bani Israel pada QS Al Maidah Ayat 72-78 dalam Perspektif Self Awareness Goleman - Nisa Shalihah; Waharjani Waharjani; Djamaluddin Perawiranegoro (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2023)
QS Al Ma'idah verses 72-78 explains the history  of Israel  clan who had bad morals towards Allah SWT and the Messenger, so that they became a people who were cursed in the Qur'an and caused hatred and sentiment  to  Jewish people. This is a challenge for the realization of religious moderation, especially for Muslims, to act toward Jews who are not hostile to Islam. Goleman in his theory of emotion competencies provides a perspective on ideal human behavior to analyze the behavior of Israel clan  as humans who have emotions and awareness. The purpose of this research is to analyze the despicable behavior of the Israel  in Goleman's self-awareness perspective. The  methods of this research is literature research (library research). Researchers use content-analysis techniques   to draw a valid conclusion based on the object of study. The results of the study concluded that  Israel  clan did not  have good self awareness at  that time. This is demonstrated by historical facts  from the Qur'an and other books which show the behavior  of Israel.